Linguistic analysis of Chinese neologisms from 2017 to 2021 - Tan, Qingqin (International Journal of Language and Literary Studies, 2024)
Lexicon is the most sensitive component of language in mirroring the changes in society. In this paper, Chinese neologisms were investigated from the perspective of their origins, characteristics and word formation, drawing the corpus of Chinese neologisms from the Language Situation in China from 2017 to 2021. Findings suggest that contemporary Chinese neologisms primarily stem from six sources: 1) new coinages; 2) existing words used with new meanings; 3) new words coined by media, magazines and news agencies; 4) internet neologisms; 5) words from dialects; 6) loanwords from other languages. In terms of the characteristics of Chinese neologisms, it is observed that in contrast to the dominance of disyllabic words in traditional Chinese, multi-syllabic words are emerging as a prominent trend in Chinese neologisms. Finally, a linguistic analysis of the corpus has been conducted to identify the formation of new words at the phonetic, morphological and semantic levels, resulting in the proposal of six categories: homophony, compounding, abbreviation, derivative words, words with letters/numbers, and rhetorical words.